2023
DOI: 10.1186/s40249-023-01087-y
|View full text |Cite
|
Sign up to set email alerts
|

Driving role of climatic and socioenvironmental factors on human brucellosis in China: machine-learning-based predictive analyses

Abstract: Background Brucellosis is a common zoonotic infectious disease in China. This study aimed to investigate the incidence trends of brucellosis in China, construct an optimal prediction model, and analyze the driving role of climatic factors for human brucellosis. Methods Using brucellosis incidence, and the socioeconomic and climatic data for 2014–2020 in China, we performed spatiotemporal analyses and calculated correlations with brucellosis inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Appropriate temperatures provide a favorable environment for Brucella and also create good conditions for host animals to breed, thereby increasing the risk of infection for those exposed to these infected animals [13]. Consistent with the findings of Faramarzi et al [43], human brucellosis incidence was positively correlated with the same month's average relative humidity in the Southern coast, the middle reaches of the Yangtze River and the Southwest, which was supported by the findings of Yang et al [18,44]. High-humidity environments can affect the enzymatic activity of Brucella and also its survival and transmission [12].…”
Section: Discussionsupporting
confidence: 74%
“…Appropriate temperatures provide a favorable environment for Brucella and also create good conditions for host animals to breed, thereby increasing the risk of infection for those exposed to these infected animals [13]. Consistent with the findings of Faramarzi et al [43], human brucellosis incidence was positively correlated with the same month's average relative humidity in the Southern coast, the middle reaches of the Yangtze River and the Southwest, which was supported by the findings of Yang et al [18,44]. High-humidity environments can affect the enzymatic activity of Brucella and also its survival and transmission [12].…”
Section: Discussionsupporting
confidence: 74%
“…Brucella is a human-animal bacterium closely associated with animal husbandry. It reproduces faster and exhibits stronger biological activity during warm seasons compared to cold seasons [ 36 ]. A Russian study found that increased temperature improves the chances of host survival and increases the risk of zoonotic infections [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of sunshine hours on the spread of brucellosis, some studies have found that extreme weather with high sunshine hours reduces the transmission of brucellosis [ 18 , 36 ]. However, our results showed that high sunshine hours increased the risk of brucellosis and had a significant lag effect.…”
Section: Discussionmentioning
confidence: 99%
“…Brucella is a human-animal bacterium closely associated with animal husbandry. It reproduces faster and exhibits stronger biological activity during warm seasons compared to cold seasons (Chen et al 2023). A Russian study found that increased temperature improves the chances of host survival and increases the risk of zoonotic infections (Revich et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It can cause skin cracking, increasing the chances of pathogen invasion(Yuan et al 2020). Our results showed that high wind velocity was not statistically signi cant in increasing the risk of brucellosis transmission.Regarding the impact of sunshine hours on the spread of brucellosis, some studies have found that extreme weather with high sunshine hours reduces the transmission of brucellosisChen et al 2023). However, our results showed that high sunshine hours increased the risk of brucellosis and had a signi cant lag effect.…”
mentioning
confidence: 99%